The Role of Sport Tourism in Improving The Economy of The Community in Kanang Village, Polewali Mandar Regency - Aswar, Nurul Fadilah; Atifah Anwar, Nur Indah; Aksir, Muh Ilham (PT Maju Malaqbi Makkarana, 2024)
This research aims to measure the economic impact of Sport Tourism in Kanang Village, Polewali Mandar Regency, West Sulawesi. This study uses a mixed methods approach and distributes questionnaires to tourist respondents, businesses, and workers. The sampling technique involves purposive sampling of 100 tourists, 30 businesses, and 30 workers. The analysis used includes the Multiplier Impact and Descriptive analysis. The research results indicate the multiplier effect value of sport tourism in the tourist area of Kanang Village, Polewali Mandar, West Sulawesi. The Keynesian Income Multiplier value is 11.99, the Ratio Income Multiplier Type I is 1.19, and the Ratio Income Multiplier Type II is 1.20. The obtained Keynesian Income Multiplier value is greater than one, which is 11.99, indicating that the activities have an economic impact on the surrounding community. This research provides insights into the contribution of Sport Tourism to the economy of Polewali Mandar Regency, which can assist the local government in promoting and developing tourism.